In praise of boredom at work. (September 2022) - Noury, Lucie; Ahuja, Sumati; Parker, Martin; Sturdy, Andrew; Tyler, Melissa
In the context of management and organisational literature, boredom has largely been seen in individual, psychological and negative terms, both for those experiencing it and for organisational outcomes. Through selective references to a wider sociological, historical and philosophical set of perspectives, we make a case here for refiguring boredom at work as a more relational and political notion. Rather than being seen as negative or trivial, we suggest that it is central to the concerns of organisation studies (and more widely) as a ambivalent everyday condition and experience. In particular, boredom is intimately linked to the project and promises of modernity and its associated effects on time, from factory industrialisation to contemporary work platforms. Both in terms of philosophical argument and applied fields such as art, literature, architecture and design, we suggest that boredom is both emancipatory/productive and alienating. Such an understanding establishes opportunities for research which would be central to the experience of contemporary paid employment and wider experience.